Potentials of cytokinesis blocked micronucleus assay in radiation triage and biological dosimetry - G. Tamizh Selvan; P. Venkatachalam (Journal of Genetic Engineering and Biotechnology)
The measurement of micronucleus (MN) in the cytokinesis-block arrested binucleated cells has been extensively used as a biomarker in many radiation biology applications in specific biodosimetry. Following radiation casualties, medical management of exposed individuals begins with triage and biological dosimetry. The cytokinesis blocked micronucleus (CBMN) assay is the alternate for the gold standard dicentric chromosome assay in radiation dose assessment. In recent years, the CBMN assay has become well-validated and emerged as a method of choice for evaluating occupational and accidental exposures scenario. It is feasible due to its cost-effective, simple, and rapid dose assessment rather than a conventional chromosome aberration assay. PubMed search tool was used with keywords of MN, biodosimetry, radiotherapy and restricted to human samples. Since Fenech and Morely developed the assay, it has undergone many technical and technological reforms as a biomarker of various applications. In this review, we have abridged recent developments of the CBMN assay in radiation triage and biodosimetry, focusing on (a) the influence of variables on dose estimation, (b) the importance of baseline frequency and reported dose–response coefficient values among different laboratories, (c) inter-laboratory comparison and (d) its limitations and means to overcome them.